Financial, Economic, and Environmental Analyses of Upgrading Reverse Osmosis Plant Fed with Treated Wastewater - Foroogh Nazari Chamaki; Glenn P. Jenkins; Majid Hashemipour (Energies, 2023)
One of the most effective strategies to mitigate water shortages worldwide is to reuse treated wastewater for freshwater production employing reverse osmosis (RO) technology. This strategy is appropriate in urban areas of arid or semi-arid regions as it can provide a sustainable and reliable water source close to the consumers. One of the drawbacks of RO is the high variability of production costs due to the electricity intensity. In addition, depending on the electricity source, it can also result in substantial environmental costs. This study showed that upgrading pumping and RO membrane systems of a wastewater reuse plant in Cyprus can significantly alleviate these drawbacks in terms cost, water recovery rate, and air pollution. The water-recovery rate of the upgraded RO plant increased from 43.2 to 75 percent, which resulted in a substantial net financial benefit due to the reduction in the quantity of wastewater purchased and the increase in potable water produced. The upgraded system also reduced the electricity requirement from 3.63 kWh/m3 to 1.92 kWh/m3. Pollution emissions decreased substantially because of the reduction in electricity requirements. The beneficiaries of these lower emission costs are the residents of Cyprus and global society. Overall, the benefit of upgrading the plant is highly attractive with more than 65 percent annual real internal rates of return in financial and economic terms. Positive net present values are realized for all the scenarios considered.